2018
DOI: 10.1177/1941738118793378
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Turf: History, Design, Maintenance, and Athlete Safety

Abstract: Modern synthetic turf is far different than when originally introduced. It requires routine maintenance, even at the level of local athletics. It is important for sports medicine personnel to be familiar with playing surface issues as they are often treating athletes at the time of injury and should maintain a level of awareness of contemporary research and practices regarding the relationships between synthetic turf and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 40 publications
(55 reference statements)
0
73
0
Order By: Relevance
“…Biomechanical tests have shown that artificial fields have the capacity to generate potentially injurious loading magnitudes before releasing the cleat in the setting of elite athletic competition compared with the release loads observed on natural surfaces. [10][11][12] Knowledge of injury patterns and characteristics of injuries can facilitate injury prevention strategies such as periodization of training and modified scheduling, refinements of the rules and styles of play, and improved strength and conditioning programs, especially as players return from the offseason to training camp and acclimate to football activity. Postinjury rehabilitation, appropriate return to play, and education of all stakeholders-players, coaches, and medical, strength, and performance personnel-is paramount to guide training, equipment selection, and other prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical tests have shown that artificial fields have the capacity to generate potentially injurious loading magnitudes before releasing the cleat in the setting of elite athletic competition compared with the release loads observed on natural surfaces. [10][11][12] Knowledge of injury patterns and characteristics of injuries can facilitate injury prevention strategies such as periodization of training and modified scheduling, refinements of the rules and styles of play, and improved strength and conditioning programs, especially as players return from the offseason to training camp and acclimate to football activity. Postinjury rehabilitation, appropriate return to play, and education of all stakeholders-players, coaches, and medical, strength, and performance personnel-is paramount to guide training, equipment selection, and other prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Suspected concussions most commonly occurred while a student was on a playground/playfield in elementary school. Proper maintenance and repair of playing surfaces 25‐27 and proper use and fit of equipment (eg, helmets) 28‐30 may help reduce the risk for concussions and other injuries during play. Prior studies note that playground use, such as playing on the monkey bars and swings, is associated with the most emergency department visits for SRR traumatic brain injuries, including concussions among elementary school‐age children in the United States 8,31 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Backing usually consists of polyester or polypropylene with a secondary layer of latex or urethane, 11 while blades are typically polyethylene. The filling material is highly variable 12 but has historically consisted of crumb rubber made of shredded, recycled Styrene-Butadiene Rubber (SBR) tires. 13,14 Other fillings include virgin materials such as Ethylene Propylene Diene Monomer (EPDM) and Thermoplastic Elastomers (TPE), or natural materials like sand, cork, coconut fibre or walnut shells.…”
Section: Introductionmentioning
confidence: 99%